Characterization of virulence and heat stress tolerance of stripe rust populations in Kansas - Gardner, Heather (Kansas State University, 2022)
Stripe rust, caused by Puccinia striiformis f.sp. tritici has caused more yield loss than any other disease in the Great Plains wheat growing region since the year 2001. Despite efforts to control the disease with genetic resistance, epidemics have increased in severity over the last decade because of changes in the regional pathogen population. There is also evidence that some members of the population are more tolerant of heat stress than historical populations of the fungus. The objectives of this research are to document virulence variation within the population of the stripe rust pathogen with attention to adult plant resistance, quantify the influence of heat stress on the pathogen, and develop models that evaluate the role of heat stress in suppressing stripe rust epidemics in Kansas. Virulence changes of the pathogen were documented with collections of Puccinia striiformis f.sp. tritici isolates from 2010 to 2021 by determining infection type and disease severity on a set of differential wheat varieties that are commonly grown in Kansas. The results indicated a trend for increasing virulence against multiple sources of genetic resistance over this time period with a few varieties displaying consistent nonrace-specific adult plant resistance. Experiments in controlled environments indicated that temperatures above 20°C increased latent period, slowed the colonization of leaf tissue, and reduced sporulation intensity of the pathogen. Isolates varied in their response to heat stress with isolates collected since 2015 often resuming sporulation sooner than those collected a decade ago. Analysis of weather conditions associated with stripe rust epidemics during the past two decades confirmed the potential of heat stress events to suppress the development of regional stripe rust epidemics and lower the risk of disease-related yield losses. The modeling results provide guidance on specific temperature conditions and time periods when heat stress is most likely to suppress stripe rust development. The overall results of this project should help guide the development of wheat varieties with durable genetic resistance to stripe rust and help wheat disease specialists evaluate the likelihood that heat stress events will slow the development of regional stripe rust epidemics.
Keywords: Stripe rust; Virulence